STRATEGI TOKOH AGAMA DAN EDUKASI KELUARGA DALAM MENGALIHKAN TRADISI MENYALAKAN MERCON PADA ANAK USIA DINI PERSPEKTIF KEISLAMAN - Meyrlin Kusumaningrum (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The tradition of lighting firecrackers during Eid al-Fitr is still deeply rooted in various regions of Indonesia, including Ponorogo, and has given rise to various social problems such as public order disturbances, the risk of accidents, and potential violations of the law. This study aims to identify and analyze the appeal strategies adopted by religious leaders and the police in controlling the firecracker tradition during Eid al-Fitr in Ponorogo, and to evaluate their effectiveness from an Islamic religious education perspective. The study uses a descriptive qualitative approach with a case study design, purposive sampling technique, and data analysis using the Miles and Huberman interactive model. The results show that the appeal strategy is implemented through three main patterns: (1) pulpit preaching and community education based on Islamic values, especially the principles of hifz al-nafs and public welfare; (2) joint patrols between the Ponorogo Police and the Ministry of Religious Affairs that integrate law enforcement with persuasive-religious communication; and (3) the issuance of a joint circular that combines formal legal authority and religious legitimacy. This collaborative strategy proved more effective than a single repressive approach, as demonstrated by a 23% reduction in firecracker incidents during Eid al-Fitr. However, its effectiveness was still partial due to cultural resistance, limited reach, and limited resources. This research confirms that sustainable social behavior change requires a consistent and participatory approach to religious education throughout the year, not just incidental interventions during festive periods.